2004
DOI: 10.2527/2004.821283x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing levels of undegradable intake protein on metabolic and endocrine factors in estrous cycling beef heifers1,2

Abstract: To determine the influence of three levels of undegradable intake protein (UIP) supplementation on metabolic and endocrine factors that influence reproduction, 23 yearling crossbred heifers (body condition score = 4.5 +/- 0.5; initial BW = 362 +/- 12 kg) were stratified by BW and assigned randomly to one of three supplements: 1) low UIP (1,135 g x heifer(-1) x d(-1); 30% CP, 115 g UIP, n = 7); 2) mid UIP (1,135 g x heifer(-1) x d(-1); 38% CP, 216 g UIP, n = 8); or 3) high UIP (1,135 g x heifer(-1) x d(-1); 46%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
13
0
4
Order By: Relevance
“…1 g of each template DNA was then used to synthesize unlabeled antisense RNA probes using MAXIscript™ in vitro transcription kit (Ambion, Austin, TX). RNA was then blotted onto nylon membrane as described previously (35). Mem-branes were blocked for 30 min in 5 ml of ULTRAhyb® (Ambion) at 68°C.…”
Section: Methodsmentioning
confidence: 99%
“…1 g of each template DNA was then used to synthesize unlabeled antisense RNA probes using MAXIscript™ in vitro transcription kit (Ambion, Austin, TX). RNA was then blotted onto nylon membrane as described previously (35). Mem-branes were blocked for 30 min in 5 ml of ULTRAhyb® (Ambion) at 68°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, the response to insulin was not observed for heifers at the JG location. Kane et al (2004) reports that insulin response to rumen undegradable protein may be influenced by environment and duration that rumen undegradable protein is offered. In addition, the responses of serum NEFA concentrations at the end of the 133-d period ending at normal weaning differed between heifers at LARRL and JG.…”
Section: Early Weaningmentioning
confidence: 99%
“…Lalman et al (1993) reported similar pregnancy rates for heifers fed a high UIP supplement vs. those fed a supplement balanced for protein degradability. Kane et al (2004) supplied postpubertal heifers 321, 216, or 115 g/d of UIP, mainly from feather meal and fishmeal. Heifers supplemented with 321 g of UIP/d had increased follicular fluid IGFBP-2 and IGFBP-4 on d 12 to 14 of the estrous cycle, lower basal serum FSH, and reduced FSH area under the curve compared with heifers fed 115 g of supplemental UIP/d, indicating high UIP intake may impair gonadotropin secretion and follicle development.…”
Section: Resultsmentioning
confidence: 99%
“…In the same study, fewer heifers fed high UIP supplements were detected in estrus during the first 21 d of the breeding season, but pregnancy rates did not differ. Additionally, supplementing postpubertal heifers with high UIP (321 g/d), mainly from feathermeal and fishmeal, decreased serum concentrations of FSH compared with heifers consuming 115 g/d UIP (Kane et al, 2004).…”
mentioning
confidence: 99%